Presentation’s effect of granulated or wet barley during the finishing phase on the productive yield of Majorcan Black Pig - Jaume J.; Joy S.; González J. (7th International Symposium on the Mediterranean Pig, 2012)
Majorcan Black Pig is an autochthonous breed in danger of extinction which is preserved due to its use to elaborate Sobrassada de Mallorca. Sustainability of this production system depends on the economic margin which is generated, thus the use of raw materials avoiding industrial processing is of a great importance. 20 castrated males were distributed in two batches, each one in a 1.5 ha plot placed contiguous, with an initial weight of 105 kg and during 86 days. The experimental design considered as the fixed effect the way the feed was presented: barley that was moistened in a water container during 24 hours vs dry granulated barley. In both cases was used the same barley origin and composition. Animals fed by dry granulated barley showed higher growth rates than those fed by moistened barley (543 vs 471 g/day, p<0.05) and higher feed intakes (2.76 vs 2.55 kg/day, p<0.05). Despite of these results regarding productive efficiency, the economic benefit generated by feeding the animals with moistened barley was 34 € per finishing pig.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)